2017
DOI: 10.1080/09638237.2016.1276540
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of emotional exhaustion, disengagement and burnout among improving access to psychological therapies (IAPT) practitioners

Abstract: Our results suggest a high prevalence of burnout among IAPT practitioners. Strategies to reduce burnout among PWPs involving reductions in workload, particularly telephone contact and increases in clinical supervision need to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 14 publications
4
99
1
Order By: Relevance
“…A previous study in a similar setting has also indicated that wider organizational and contextual factors, such as working overtime, increased telephone-based work, and infrequent access to clinical supervision are implicated in occupational burnout (Westwood et al, 2017). Therapists' resilience may also be an important determinant of clinical outcomes (Green et al, 2014;Pereira et al, 2017).…”
Section: Main Findingsmentioning
confidence: 92%
“…A previous study in a similar setting has also indicated that wider organizational and contextual factors, such as working overtime, increased telephone-based work, and infrequent access to clinical supervision are implicated in occupational burnout (Westwood et al, 2017). Therapists' resilience may also be an important determinant of clinical outcomes (Green et al, 2014;Pereira et al, 2017).…”
Section: Main Findingsmentioning
confidence: 92%
“…The high emotional demands of psychotherapeutic work have been extensively documented (e.g., D'Souza, Egan, & Rees, 2011;Farber, 1983;Westwood, Morison, Allt, & Holmes, 2017). Psychological practitioners are exposed to significant vicarious distress and may face limited resources and excessive demands (Rupert & Morgan, 2005).…”
Section: Psychological Practitioner Well-beingmentioning
confidence: 99%
“…Many of the contextual factors affecting intervention delivery such as staff shortages, inadequate training and supervision, a poorly specified intervention and lack of systems for monitoring competence and treatment adherence (Morse, Salyers, Rollins, Monroe‐DeVita, & Pfahler, ), not only appear to have a negative impact on the quantity and quality of intervention delivery but have also been associated with staff burnout. Staff burnout results in decreased motivation and poorer interactions with patients and constitutes a further threat to healthcare quality and patient safety (Salyers et al, ; Westwood, Morison, Allt, & Holmes, ). Interventions that are delegated to less experienced practitioners may also compromise comprehensive assessment, patient engagement, and intervention effectiveness (Scott, ).…”
Section: Discussionmentioning
confidence: 99%